Comparison of value system between Slovene olympic athletes and national football team - Pinter, Stanislav (Kinesiologia Slovenica, 2003)
The main aim of this research was to determine the most important values of Slovene elite athletes, which participated at the most influential competitions. Furthermore we were interested in possible differences in value system according to participation in team or individual sport disciplines. The sample of individual athletes was composed by 31 Slovene Olympic men athletes (Sydney 2000) whereas the sample of team athletes was represented by 19 Slovene football players, which also participated in World football championship (Korea 2002). In the research was used Musekćs value scale, which measures 54 basic values and also specific value orientations, value types and value uppercategories. Data were computed by means of basic descriptive statistics and one-way analysis of variance. Bigger, statisticaly important differences between the two groups were noticed in valuation of apolonic values and among them mostly of moral ones. At more specific level of value system, traditional-moral, democratic, patriotic, religious and ecological value orientations were those where the biggest differences were shown.
Keywords: psihologija športa; raziskave; slovenski športniki; vrednote; vrednotni sistemi; vrhunski športniki